Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

Segmented flow synthesis of Ag nanoparticles in spiral microreactor: role of continuous and disperzsed phase - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, Amol A. (Chemical Engineering Journal, 2012)
This work focuses on understanding the effect of segmented flow on the nanoparticle size distribution in a unidirectionally expanding spiral microreactor, where secondary flows are prevalent in the absence of segmentation. Stearic acid sophorolipid reduced/capped Ag NPs were synthesized in the aqueous phase and air or kerosene was used as inert phases for creating the gas-liquid and liquid-liquid segmented flow, respectively. While, in one case the reactant phase is in the form of dispersed phase slugs, in the other case it is in the form of continuous phase, each exhibiting a different behavior. The slug sizes and the slip velocity, both of which govern the nature of internal mixing in the reactant phase slug controlled the nanoparticle size distribution. This observation was consistent for both, gas-liquid and liquid-liquid segmented flows. The micromixer having smaller orifice diameter yielded smaller slugs and also a narrow particle size distribution. In general, the particle sizes were much smaller for gas-liquid flow rather than for liquid-liquid flow. Because of the unidirectionally expanding spiral geometry of the channel, at any given condition, unsteady behavior of slugs due to continuously varying radius of curvature results in variation in the slip velocity along the length of microchannel. This effect was seen to further narrow the particle size distribution than alone by the segmented flow. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ag nanoparticles; Segmented flow synthesis; Sophorolipid; Spiral microreactor

Impinging jet micromixer for flow synthesis of nanocrystalline MgO: role of mixing/impingement zone - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Industrial & Engineering Chemistry Research, 2013)
Continuous flow synthesis of nanomaterials via sol-gel process using microreactors has not received much attention. For the synthesis of gels where the reaction time is of the order of few seconds to few tens of seconds, microchannel reactors are an excellent processing option. However since a `gel' does not `flow' easily, making it in a microchannel usually clogs the microchannel. We envisaged that by using an impinging jet micromixer, where the two reactants impinge and collide to form a mixing zone outside the micromixer, this problem could be circumvented. Here we report a successful implementation of continuous flow synthesis of metal oxides formed by the rapid sol-gel process taking the nanocrystalline MgO (NC-MgO) as a specific example. Furthermore, we clearly demonstrate that the nature of the mixing zone formed by the impinging jets governs the surface area of the product. Specific flow rate and impingement angle are identified that yield high surface area materials.

Surfactant-free synthesis of anisotropic gold nanostructures: can dicarboxylic acids alone act as shape directing agents? - Kumar, D. V. Ravi; Kumavat, S. R.; Chamundeswari, V. N.; Patra, Partha Pratim; Kulkarni, A. A.; Bhagavatula L. V. Prasad (RSC Advances, 2013)
The present study describes the synthesis of gold nanostructures using different dicarboxylic (viz. oxalic, malonic, succinic, glutaric and adipic) acids as reducing agents in the absence of any other additives or surfactants. Various anisotropic structures such as kites, tadpoles, triangular/hexagonal plates, and twinned particles were seen to evolve depending on the molar ratio of dicarboxylic acid to HAuCl4 used. It was also demonstrated that gold nanostructure formation is hampered as the chain length/distance between two carboxylic acid groups increases. Among the various structures obtained the kite like structures displayed the largest surface enhanced Raman enhancement factors.

Synthesis of triangular gold nanoplates: role of bromide ion and temperature - Kumar, D. V. Ravi; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2013)
Synthesis of noble metal triangular nanoplates is a kinetically controlled process in which temperature and packing defects play a major role. Nucleation and growth process of kinetically controlled reaction can be greatly influenced by temperature affecting the yield and edge length of the triangles. Through a conventional batch mode process, here we study the effect of temperature on nucleation and growth of gold triangular nanoplates and obtain some insight of the temperature effects on the final yield and edge length of triangles. The role of Br- ions in the synthesis of triangular nanoplates is studied by varying the amount of CAB and by replacing the CTAB with HBr. The results show that, while CTAB controls the edge length and yield of triangles, its use is not mandatory to attain plate like morphology. Finally we show that, while the initial temperature of the reaction mixture governs the nucleation rate and the rate of temperature rise governs the growth rate of particles, they along with the concentration of Br- ions control the edge length and yield. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Halide ion effect; heat transfer; Kinetically controlled; Nature of gold precursor complex; Nucleation and growth; Optical properties

Microfluidic platform for continuous flow synthesis of triangular gold nanoplates - Kumar, D. V. Ravi; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
A microfluidic platform for the continuous flow synthesis of triangular gold nanoplates with and without surfactants is developed. The temperature profile in the microchannel, residence time and composition have been studied to understand effect of these parameters on the yield of the triangular nanoplates and were optimized for obtaining maximum yield of triangles. The flow synthesis approach has been demonstrated where the Br- ions can be supplied to the reaction mixture either from the surfactant viz. Cetyl trimethylammonium bromide (CTAB) or even from HBr. Apart from the Br- ions, the temperature gradient at the inlet of the continuous flow reactor is one of the key parameter that affects the yield of the triangular nanoplates. Finally we establish that with a right combination of the controlling parameters abetter yield of the Au nanotriangles by flow methods can be achieved even in the absence of surfactant. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Flow synthesis; microreactor; Nucleation kinetics; Surfactants

Agro-industrial wastes for production of biosurfactant by bacillus subtilis ANR 88 and its application in synthesis of silver and gold nanoparticles - Rane, Ashwini N.; Baikar, Vishakha V.; Kumar, D. V. Ravi; Deopurkar, Rajendra L. (Frontiers in Microbiology, 2017)
Biosurfactants, surface-active amphiphilic compounds, despite having a wide range of applications, have a high cost of production, which severely restricts their use. For cheaper production of biosurfactant, we investigated the potential of the indigenously isolated biosurfactant producing organism, Bacillus subtilis ANR 88, to grow on different cheap carbon sources (molasses, whey, and extracts of potato peels, orange peels, banana peels, and bagasse). We found that, B. subtilis ANR 88 used significant amounts of total sugar to produce cell biomass and biosurfactant. The biosurfactant production in minimal medium containing glucose as sole source of carbon was 0.207 g/l and the same with molasses as carbon source was 0.241 g/l. With whey as carbon source, isolate failed to produce biosurfactant. Amongst the extracts of the agro-wastes, the extracts of bagasse and orange peels gave 0.127 and 0.089 g/l of biosurfactant respectively. One-variable-at-a-time (OVAT) studies carried out to optimize the production of biosurfactant by B. subtilis ANR 88 resulted into maximum biosurfactant yield of 0.513 g/l in medium: molasses 4%, ammonium ferric citrate 0.25%, pH 7. Plackett-Burman design based statistical method for optimization increased the production of biosurfactant to 0.746 g/l, which is 3.6-fold of that produced on glucose. The biosurfactant produced by B. subtilis ANR 88 was analyzed by Fourier Transform Infrared Spectroscopy (FT-IR); it showed that the biosurfactant contained alkyl as well as peptide groups. The biosurfactant of B. subtilis ANR 88 was found effective in the synthesis of silver as well as gold nanoparticles in the total absence of conventional chemical reducing agents. Interestingly, nanoparticles produced were almost uniform in their size and shapes i.e., spherical silver (4-18 nm) and hexagonal gold nanoparticles (40-60 nm), as evident in TEM images.